Mapping the linguistic landscape of Kuala Lumpur / Misyana Susanti Husin ... [et al.] - Husin, Misyana Susanti; Ariffin, Kamisah; de Mello, Geraldine; Omar, Nur Hidayatulshima; Anuardin, Aini Andria Shirin (Akademi Pengajian Bahasa, 2019)
Linguistic landscape (LL) refers to the visibility and salience of languages on public and commercial signs in a given territory or region. The highest density of signs can be found in cities and towns, particularly in the main shopping streets and industrial areas. This study is a synchronic analysis of digitally photographed commercial shop signs in three selected regions of Kuala Lumpur that focuses on the patterns of the language use. Findings reveal bilingual shop signs dominated the shopping streets in the areas adjacent to and within Kuala Lumpur and English being more prevalent than the national language or other languages. There was also visibility of foreign languages that offers linguistic diversity in the cityscapes. In summary, multilingualism in the areas boils down to different languages being used and functioning in differing ways.